2018
DOI: 10.1016/j.ultsonch.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antimicrobial activity of ZnO nanofluids in sonophotocatalysis and its mechanism

Abstract: This study investigated the inactivation efficiency of ZnO nanofluids against E. coli in sonophotocatalysis with the aeration of nitrogen, oxygen, argon and their mixtures. The results showed that inactivation efficiency was increased when aeration was combined with sonophotocatalysis. Addition of different types of gases could lead to the different inactivation efficiency. The inactivation efficiencies were shown in the following order: no aeration < nitrogen < argon < oxygen < Ar/O(3:7) < Ar/O(7:3) < Ar/O(5:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, the majority of the successful applications of sonophotocatalysis have been focused on environmental remediation applications, especially for waste-water treatment against toxic organic compounds, through uncontrollable advanced oxidation processes (AOPs). [36][37][38][39][40] The reported cases of successful combination of photo-and sonochemistry as a Hybrid Advanced Oxidation Process (HAOP) toward specific selective catalytic reactions and valorization of biomass are limited due to the complexity of manipulating the formed active oxygen species, developing an appropriate sonophotoreactor and of course an appropriate sonophotocatalyst. 11 Regarding the latter issue, the ultimate goal is to avoid the usage of precious noble and/or rare-earth metal-based catalysts, addition of hazardous and non-reusable chemicals, and the need for harsh experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the successful applications of sonophotocatalysis have been focused on environmental remediation applications, especially for waste-water treatment against toxic organic compounds, through uncontrollable advanced oxidation processes (AOPs). [36][37][38][39][40] The reported cases of successful combination of photo-and sonochemistry as a Hybrid Advanced Oxidation Process (HAOP) toward specific selective catalytic reactions and valorization of biomass are limited due to the complexity of manipulating the formed active oxygen species, developing an appropriate sonophotoreactor and of course an appropriate sonophotocatalyst. 11 Regarding the latter issue, the ultimate goal is to avoid the usage of precious noble and/or rare-earth metal-based catalysts, addition of hazardous and non-reusable chemicals, and the need for harsh experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments carried out in sonophotocatalytic degradation of E. coli in different environments showed that the inactivation efficiency of ZnO nanofluids under purging with nitrogen, oxygen, argon, and their mixtures led to different inactivation efficiency being correlated to the production of hydroxyl radicals and the inactivation mechanism. 1017 It varied in the following order: no aeration < nitrogen < argon < oxygen < Ar/O 2 (3:7) < Ar/ O 2 (7:3) < Ar/O 2 (5:5). The deposition of ZnO nanoparticles onto multiwalled carbon nanotubes afforded an increased absorbance of photocatalyst in the visible-light region that correlates with an enhanced degradation of Rhodamine B dye.…”
Section: Znmentioning
confidence: 99%
“…The atmosphere in which the sono­photodegradation is carried out exerts an important effect as well. Experiments carried out in sono­photocatalytic degradation of E. coli in different environments showed that the inactivation efficiency of ZnO nanofluids under purging with nitrogen, oxygen, argon, and their mixtures led to different inactivation efficiency being correlated to the production of hydroxyl radicals and the inactivation mechanism . It varied in the following order: no aeration < nitrogen < argon < oxygen < Ar/O 2 (3:7) < Ar/O 2 (7:3) < Ar/O 2 (5:5).…”
Section: Innovative Combined Solar Driven Technologies: Advantages An...mentioning
confidence: 99%
“…However, sonophotocatalysis, through advanced oxidation processes (AOPs), has been most widely used in environmental remediation, especially waste-water treatment. 17–22…”
Section: Introductionmentioning
confidence: 99%